Distributing the Power of a Government to Enhance the Privacy of Voters - Benaloh, Josh; Yung, Moti (Principles of Distributed Computing, 1986)
In this paper, we distribute the functions of the government in the cryptographic election scheme of [CoFi85]. In so doing, we are able to achieve privacy of individual votes in a much stronger sense without giving up any of the previously attained properties of robustness or veriability. This gives an electronic mechanism for holding a large-scale election amongst untrusted parties which is far more useful in "realworld" applications than the previous scheme.